2018
DOI: 10.1021/acs.chemmater.8b01549
|View full text |Cite
|
Sign up to set email alerts
|

Tolerance Factor and Cooperative Tilting Effects in Vacancy-Ordered Double Perovskite Halides

Abstract: Lattice dynamics and structural instabilities are strongly implicated in dictating the electronic properties of perovskite halide semiconductors. We present a study of the vacancy-ordered double perovskite Rb2SnI6 and correlate dynamic and cooperative octahedral tilting with changes in electronic behavior compared to those of Cs2SnI6. Though both compounds exhibit native n-type semiconductivity, Rb2SnI6 exhibits carrier mobilities that are reduced by a factor of ∼50 relative to Cs2SnI6. From synchrotron powder… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
123
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(141 citation statements)
references
References 68 publications
(127 reference statements)
8
123
0
Order By: Relevance
“…Their crystal structure is depicted by Maughan et al, as shown in Figure 9a,b. Although there are some conflicting reports [88,112,124,169] on the room temperature carrier mobility of Cs 2 SnI 6 , the origin of conductivity in this compound has been hypothesized to stem from (a) the possession of dispersive conduction band states and (b) the presence of iodine vacancies. Cs 2 SnI 6 compound exhibits intrinsic n-type electrical conductivity and other fascinating features such as direct bandgap, air and moisture stability, and strong visible light absorption.…”
Section: Vacancy Ordered Halide Double Perovskitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Their crystal structure is depicted by Maughan et al, as shown in Figure 9a,b. Although there are some conflicting reports [88,112,124,169] on the room temperature carrier mobility of Cs 2 SnI 6 , the origin of conductivity in this compound has been hypothesized to stem from (a) the possession of dispersive conduction band states and (b) the presence of iodine vacancies. Cs 2 SnI 6 compound exhibits intrinsic n-type electrical conductivity and other fascinating features such as direct bandgap, air and moisture stability, and strong visible light absorption.…”
Section: Vacancy Ordered Halide Double Perovskitesmentioning
confidence: 99%
“…[169] The polaron characteristics and charge transport behavior in vacancy-ordered double perovskites can be tuned by introducing cooperative octahedral tilting distortions. [169] The polaron characteristics and charge transport behavior in vacancy-ordered double perovskites can be tuned by introducing cooperative octahedral tilting distortions.…”
Section: Wwwadvancedsciencenewscommentioning
confidence: 99%
“…We used these metrics to estimate the limit to Rb + doping of CsPbBr 3 ( t = 0.92) with Rb + to increase the bandgap. Finite Rb + incorporation results in further tilting of the PbX 6 octahedra, reducing the overall orbital overlap and hence opening up the bandgap of CsPbBr 3 while simultaneously reducing the tolerance factor . However, it has been reported that an upper bound of 70% Rb + exists in a mixed cation perovskite QD, as pure RbPbBr 3 does not exist under ambient conditions …”
Section: Peled Electroluminescence Performance Metricsmentioning
confidence: 99%
“…Substitution of Cs + ion with relatively smaller Rb + ion in the vacancy‐ordered double perovskite Cs 2 SnI 6 has been investigated, with significant changes in structure and electronic behavior observed . The conductivity measurement of Rb 2 SnI 6 indicates that it is a natural n‐type semiconductor, but the carrier mobility is reduced by about 50 times compared with Cs 2 SnI 6 .…”
Section: Materials and Structuresmentioning
confidence: 99%